Neuropeptide Y: An Update on the Mechanism Underlying Chronic Intermittent Hypoxia-Induced Endothelial Dysfunction - Li, Mei-mei; Zheng, Yan-li; Wang, Wan-da; Lin, Shu; Lin, Hui-li (Frontiers in Physiology, 2021)
Endothelial dysfunction (ED) is a core pathophysiological process. The abnormal response of vascular endothelial (VE) cells to risk factors can lead to systemic consequences. ED caused by intermittent hypoxia (IH) has also been recognized. Neuropeptide Y (NPY) is an important peripheral neurotransmitter that binds to different receptors on endothelial cells, thereby causing ED. Additionally, hypoxia can induce the release of peripheral NPY; however, the involvement of NPY and its receptor in IH-induced ED has not been determined. This review explains the definition of chronic IH and VE function, including the relationship between ED and chronic IH-related vascular diseases. The results showed that that the effect of IH on VE injury is mediated by the VE-barrier structure and endothelial cell dysfunction. These findings offer new ideas for the prevention and treatment of obstructive sleep apnea syndrome and its complications.